2017
DOI: 10.3345/kjp.2017.60.12.403
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low-dose intravenous bisphosphonate treatment on osteoporosis in children with quadriplegic cerebral palsy

Abstract: PurposeQuadriplegic children with cerebral palsy are more susceptible to osteoporosis because of various risk factors that interfere with bone metabolism. Pamidronate is effective for pediatric osteoporosis, but there are no guidelines for optimal dosage or duration of treatment in quadriplegic children with osteoporosis. We aimed to evaluate the efficacy of low-dose pamidronate treatment in these patients.MethodsTen quadriplegic patients on antiepileptic drugs (6 male, 4 female patients; mean age, 10.9±5.76 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…Therefore, calcium and vitamin D supplementation has become a widespread practice for preventing hypocalcemia during treatment with pamidronate [ 4 ]. Pamidronate treatment can cause an increase in 25(OH) 2 D 3 level and a decrease in alkaline phosphatase [ 27 ]; however, no significant changes in biochemical parameters were detected in the present study.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Therefore, calcium and vitamin D supplementation has become a widespread practice for preventing hypocalcemia during treatment with pamidronate [ 4 ]. Pamidronate treatment can cause an increase in 25(OH) 2 D 3 level and a decrease in alkaline phosphatase [ 27 ]; however, no significant changes in biochemical parameters were detected in the present study.…”
Section: Discussioncontrasting
confidence: 83%
“…Bone turnover markers can be helpful in monitoring the efficacy of treatment [ 29 ]. Previous studies have reported an increase in serum osteocalcin (which reflects increased bone formation) and a decrease in urine N-terminal telopeptide (which indicates decreased bone resorption) during pamidronate treatment [ 27 ]. However, no bone turnover markers were included in the present study due to lack of data.…”
Section: Discussionmentioning
confidence: 99%
“…26) Several studies of secondary osteoporosis and bisphosphonate treatment have been conducted since 2002 (Supplementary Table 1). [13][14][15][16][17]27) In each study, patients received bisphosphonate treatments of various durations and dosages. The results of the studies showed that pamidronate could improve the BMD of patients with secondary osteoporosis and various underlying diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Since bisphosphonates were first suggested as a treatment for primary osteoporosis in children with osteogenesis imperfecta in 1998, these therapies have been widely used as standard therapy for children with osteoporosis and pathologic fractures. 10) Previous studies have shown that bisphosphonates increase BMD [12][13][14][15][16] and decrease the risk of fractures in children with low BMD. 17) Many children with pathologic fractures have experienced improved disease conditions and quality of life after bisphosphonate treatment.…”
Section: Effectiveness and Safety Of Pamidronate Treatment In Nonambu...mentioning
confidence: 99%
“…Pamidronate remains the most thoroughly investigated bisphosphonate for intravenous administration in children with fourteen studies (nine in children with CP) included in this review. Several studies used 15 mg/kg/year while the most recent studies document that dosages as low as 4.12 mg/kg/year 34 and 2.13–8.80 mg/kg/year 58 may be effective in children with CP. We were able to meta‐analyse five studies on children with CP who were treated with pamidronate.…”
Section: Discussionmentioning
confidence: 99%